Frequency and Acceptability of Adverse Events After Anterior Cervical Discectomy and Fusion: A Survey Study From the Cervical Spine Research Society. Issue 5 (June 2018) - Wilson, Jefferson R.; Radcliff, Kris; Schroeder, Gregory; Booth, Madison; Lucasti, Christopher; Fehlings, Michael; Ahmad, Nassr; Vaccaro, Alexander; Arnold, Paul; Sciubba, Daniel; Ching, Alex; Smith, Justin; et al.
Abstract : Purpose: Anterior cervical discectomy and fusion has a low but well-established profile of adverse events. The goal of this study was to gauge surgeon opinion regarding the frequency and acceptability of these events. Methods: A 2-page survey was distributed to attendees at the 2015 Cervical Spine Research Society (CSRS) meeting. Respondents were asked to categorize 18 anterior cervical discectomy and fusion–related adverse events as either: "common and acceptable, " "uncommon and acceptable, " "uncommon and sometimes acceptable, " or "uncommon and unacceptable." Results were compiled to generate the relative frequency of these responses for each complication. Responses for each complication event were also compared between respondents based on practice location (US vs. non-US), primary specialty (orthopedics vs. neurosurgery) and years in practice. Results: Of 150 surveys distributed, 115 responses were received (76.7% response rate), with the majority of respondents found to be US-based (71.3%) orthopedic surgeons (82.6%). Wrong level surgery, esophageal injury, retained drain, and spinal cord injury were considered by most to be unacceptable and uncommon complications. Dysphagia and adjacent segment disease occurred most often, but were deemed acceptable complications. Although surgeon experience and primary specialty had little impact on responses, practice location was found to significantly influence responses for 12 of 18 complications, with non-US surgeons found to categorize events more toward the uncommon and unacceptable end of the spectrum as compared with US surgeons. Conclusions: These results serve to aid communication and transparency within the field of spine surgery, and will help to inform future quality improvement and best practice initiatives.